Pemanfaatan Moringa oleifera sebagai Produk Olahan Sehat dan Bernilai Ekonomis bagi Masyarakat di Kecamatan Ratu Samban Kota Bengkulu di Tengah Pandemi Covid-19 - Meilani Belladona; Janusi Waliamin (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2021)
The Covid-19 pandemic era greatly affected the economy of residents in Ratu Samban District, Bengkulu City, Bengkulu Province. The problems encountered are that family’s income is very dependent on the business run by residents and the narrow yard of the house becomes an obstacle for residents to plant various types of plants that can be sold. The purpose of this service was to increase the knowledge of citizens to find new sources of income from the Moringa plant (Bengkulu local language: Remunggai) so that they were skilled in processing the remunggai plant to be useful and of economic value for the community. The method used was counseling about the remunggai plant and training in making processed products from the remunggai leaves. The products produced of this activity were roll cakes and remunggai candy which could be consumed by themselves or sold to earn additional income. The knowledge of residents about the remunggai plant has increased and the skills of residents in making processed products have also increased so that it was expected to increase people's income.